Unraveling the enigma of sclerosing encapsulating peritonitis: a comprehensive review - Witcha Vipudhamorn; Tawan Juthasilaparut; Pawit Sutharat; Suwan Sanmee; Ekkarin Supatrakul; Sayanan Chowsilpa; Kraipop Wongwaiyut; Rujee Rattanasathien (Annals of Coloproctology)
Sclerosing encapsulating peritonitis (SEP) is a rare but serious condition characterized by the progressive formation of a dense fibrous sheath encasing the small bowel within the peritoneal cavity. This review provides a comprehensive overview of the current understanding of SEP, focusing on its etiology, clinical presentation, diagnostic modalities, and management strategies. SEP can be classified into primary and secondary forms, each with distinct etiologies and treatment approaches. Primary SEP typically presents with acute or subacute bowel obstruction symptoms, necessitating surgical intervention to excise the fibrous sheath and relieve the obstruction. Secondary SEP often occurs in patients undergoing peritoneal dialysis, with cessation of dialysis being a key component of management. Medical treatments, including corticosteroids, immunosuppressive agents, and nutritional support, may complement surgical intervention, particularly in cases of secondary SEP. Advanced imaging techniques and personalized medicine approaches show promise in improving diagnostic accuracy and tailoring treatment strategies to individual patients. Future research directions include investigating targeted pharmacological therapies, exploring minimally invasive surgical techniques, and conducting long-term follow-up studies to evaluate treatment efficacy and disease recurrence. Multidisciplinary care teams play a crucial role in the comprehensive management of SEP, emphasizing collaboration among various specialties to optimize patient outcomes.